Employee Turnover Behavior in Nepalese Commercial Banks - Prakash Shrestha; Guna Raj Chhetri; Babu Ram Panthi (Journal of Balkumari College, 2025)
This study focused on employee turnover behavior specifically within Nepalese commercial banks. The main goal was to examine the key factors influencing why employees leave their jobs in service sector organizations. The analysis centered around five important areas: workload and job stress, job satisfaction, career development, working environment, and compensation and benefits. The results revealed that all these factors significantly shape employees’ intentions to quit their current positions. Among these, compensation and benefits had the strongest impact, suggesting that employees tend to stay longer in organizations that provide fair, transparent, and competitive pay and rewards. Workload and job stress also played a crucial role, showing that heavy workloads and poorly managed stress increase the likelihood of employees wanting to leave. The findings also align with other studies, reinforcing the idea that employee turnover is a complex issue influenced by a mix of stress management, career growth opportunities, compensation, work environment, and social support. The differences found across various studies highlight the importance of considering the unique circumstances and context of each organization when developing strategies to retain employees. This research adds to the existing knowledge by confirming global patterns within the Chitwan context, while also pointing out local specifics—such as the particularly strong influence of compensation and workload management on employee turnover decisions in this area.